Rethinking rubbish - McCormack, Jessica (School of Architecture, Planning and Geomatics, 2024)
Industrial processes forms have dominated the landscape with their linear and degenerative processes. The imposition of these forms in the landscape is exemplified by the industrial area adjacent to the harbour in Cape Town, which was located on the coastline prior to the reclamation of the coastline between 1941 and 1962. These linear and degenerative industrial processes disregard the Second Law of Thermodynamics, which states that entropy of a system increases. This has resulted in unnecessary resource consumption, as well as a permeation of pollutants into the environment. Regenerative design seeks to re-mediate this and reconnect us to nature. Recycling is an example of an attempt at regenerative design. The Woodstock Drop off Facility is a recycling drop off point where domestic and waste from small retailers and builders is brought before it is sorted and dispersed to various recycling plants and the Vissershoek landfill. It is located in the industrial area and offers oppourtunity to connect users to material flows and processes, which are otherwise forgotten. Stremke et al (2011) conclude that dispersal and mixing are two causes of increases in entropy. In order to gain an understanding of the potential role of the Woodstock Drop off Facility in more regenerative material flows, The Woodstock Drop off Facility is assessed with regards to dispersal and mixing. The aim of this study is to assess the site's potentials in terms of reconnecting the user to material flows and natural systems, as well as an assessment pf how regenerative recycling processes actually are. Sorting and Dispersal are the major functions of the Woodstock Drop off Facility. Stremke et al (2011) argue that as materials become more mixed and dispersed, they become more entropic. This study aims to evaluate this landscape of mixing and dispersal in terms of entropy and therefore assess the regenerative potentials of the site